PERHITUNGAN CHANGE ORDER PROYEK JALAN DI BANTEN - Waty, Mega; Sulistio, Hendrik (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
ABSTRACTChange orders include a number of variants in the scope of work namely the amount of material, design errors, and price changes. This paper discusses change orders in a road construction project in Banten by investigating the causes, studying their effects on the project, and identifying the beneficiaries. The study used five road projects as actual case studies and the questionnaire used a six-point Likert Scale. To determine the ranking of factors that influence the causes of change orders, the effect of change orders and the factors that benefit from change orders are used the Relative Importance Index (RII) calculation. The most important effects of change orders on projects are found to be schedule delays, cost overruns and disputes. The contractor as the party that benefits the most from the change order is followed by the consultant and then the owner. Keywords: change order; road project; Relative Importance Index (RII) ABSTRAK Change order mencakup sejumlah varian dalam ruang lingkup pekerjaan yakni jumlah material, kesalahan desain, dan perubahan harga. Makalah ini membahas change order dalam proyek konstruksi jalan di Banten dengan menyelidiki penyebab, mempelajari efeknya pada proyek, dan mengidentifikasi pihak-pihak yang diuntungkan. Penelitian menggunakan lima proyek jalan sebagai studi kasus aktual dan Kuisoner menggunakan Skala Likert Enam poin. Untuk mengetahui peringkat faktor yang mempengaruhi penyebab change order, efek change order dan faktor yang diuntungkan dari change order digunakan perhitungan Relative Importance Index (RII). Efek terpenting dari change order pada proyek ditemukan adalah penundaan jadwal, pembengkakan biaya dan perselisihan. Kontraktor selaku pihak yang paling diuntungkan dari change order diikuti oleh konsultan dan kemudian owner.